2019
DOI: 10.1021/acs.jchemed.8b00846
|View full text |Cite
|
Sign up to set email alerts
|

Drawing a New Scientist: Why I Come Out to My Chemistry Class

Abstract: Encouraging the persistence of underrepresented populations in STEM begins in gateway science courses like general chemistry. In these courses, success often depends on students’ ability to affirm their identity and sense of belonging in the science classroom. General chemistry suffers from an unfortunate lack of diverse role models; however, the instructor can use personal identity to help remedy this problem. Actively affirming identity in the classroom allows students from all backgrounds to feel like they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…Research shows that having role models that share aspects of your identity such as race and gender supports students' persistence and academic performance in math (Drury, Siy, & Cheryan, 2011;Marx & Roman, 2002). While there have yet to be studies to document the same effect on academic performance and persistence for queer students there are a growing number of STEM professionals advocating for coming out in math and science to provide visible role models for youth (Barres, Montague-hellen, & Yoder, 2017;Esposito, 2019;Knezz, 2019;Restar & Operario, 2019;.…”
Section: Queer Acceptance and Visibility In Math 19mentioning
confidence: 99%
“…Research shows that having role models that share aspects of your identity such as race and gender supports students' persistence and academic performance in math (Drury, Siy, & Cheryan, 2011;Marx & Roman, 2002). While there have yet to be studies to document the same effect on academic performance and persistence for queer students there are a growing number of STEM professionals advocating for coming out in math and science to provide visible role models for youth (Barres, Montague-hellen, & Yoder, 2017;Esposito, 2019;Knezz, 2019;Restar & Operario, 2019;.…”
Section: Queer Acceptance and Visibility In Math 19mentioning
confidence: 99%
“…While STEM educators believe in inclusive pedagogy, they often avoid discussing sociopolitical, culturally sensitive topics due to the enormity of course content, and/or an inherent discomfort in facilitating these discussions (8). As a result, instruction in a STEM classroom is typically objective, data-driven, and focused on scientific concepts (e.g., gene regulation) (9). Nonetheless, instructors who have successfully executed such discussions provide evidence that socio-scientific issues-based instruction fosters content learning, improves performance on high-stakes tests (10), and increases reflective judgment and epistemological growth (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Another strategy targeting social factors of learning is creating a classroom culture that respects and values students’ diverse racial, gender, and socioeconomic identities. Studies showed that such a classroom culture improved students’ sense of belonging and retention in chemistry courses. ,, On the basis of a review of evidence-based practices, White and colleagues suggested that instructors’ enactment of a growth mindset and validation of students’ identities can promote students’ sense of belonging and positively impact performance and retention of URM students. Knezz described her experiences from sharing her own identity with students in chemistry classes and advocated that actively affirming identity in the classroom allowed students from all backgrounds to feel that they belong in science.…”
Section: Resultsmentioning
confidence: 99%
“…Studies showed that such a classroom culture improved students’ sense of belonging and retention in chemistry courses. ,, On the basis of a review of evidence-based practices, White and colleagues suggested that instructors’ enactment of a growth mindset and validation of students’ identities can promote students’ sense of belonging and positively impact performance and retention of URM students. Knezz described her experiences from sharing her own identity with students in chemistry classes and advocated that actively affirming identity in the classroom allowed students from all backgrounds to feel that they belong in science. In a high school classroom, Patchen and Smithenry showed that engaging students in different participant structures (students work as individuals, in small groups, and as the whole group) makes all students feel they belong to a learning community.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation